What Is Important When Making Treatment Decisions in Metastatic Breast Cancer? A Qualitative Analysis of Decision‐Making in Patients and Oncologists. (14th March 2019) - Rocque, Gabrielle B.; Rasool, Aysha; Williams, Beverly R.; Wallace, Audrey S.; Niranjan, Soumya J.; Halilova, Karina I.; Turkman, Yasemin E.; Ingram, Stacey A.; Williams, Courtney P.; Forero‐Torres, Andres; Smith, Tom; Bhatia, Smita; et al.
Abstract: Background: Metastatic breast cancer (MBC) is an ideal environment for shared decision‐making because of the large number of guideline‐based treatment options with similar efficacy but different toxicity profiles. This qualitative analysis describes patient and provider factors that influence decision‐making in treatment of MBC. Materials and Methods: Patients and community oncologists completed in‐person interviews. Academic medical oncologists participated in focus groups. Interviews and focus groups were audio‐recorded, transcribed, and analyzed using NVivo. Using an a priori model based on the Ottawa Framework, two independent coders analyzed transcripts using a constant comparative method. Major themes and exemplary quotes were extracted. Results: Participants included 20 patients with MBC, 6 community oncologists, and 5 academic oncologists. Analysis of patient interviews revealed a decision‐making process characterized by the following themes: decision‐making style, contextual factors, and preferences. Patient preference subthemes include treatment efficacy, physical side effects of treatment, emotional side effects of treatment, cognitive side effects of treatment, cost and financial toxicity, salience of cutting‐edge treatment options (clinical trial or newly approved medication), treatment logistics and convenience, personal and family responsibilities, treatment impact on daily activities, participation in self‐defining endeavors, attending important events, and pursuing important goals. Physician decisions emphasized drug‐specific characteristics (treatment efficacy, side effects, cost) rather than patient preferences, which might impact treatment choice. Conclusion: Although both patients with MBC and oncologists considered treatment characteristics when making decisions, patients' considerations were broader than oncologists', incorporating contextual factors such as the innovative value of the treatment and life responsibilities. Differences in perspectives between patients and oncologists suggests the value of tools to facilitate systematic communication of preferences in the setting of MBC. Implications for Practice: Both patients with metastatic breast cancer (MBC) and oncologists emphasized importance of efficacy and physical side effects when making treatment decisions. However, other patient considerations for making treatment decisions were broader, incorporating contextual factors such as the logistics of treatments, personal and family responsibilities, and ability to attend important events. Furthermore, individual patients varied substantially in priorities that they want considered in treatment decisions. Differences in perspectives between patients and oncologists suggest the value of tools to facilitate systematic elicitation of preferences and communication of those preferences to oncologists for integration into decision‐making in MBC. Abstract : Shared decision‐making occurs when a patient is informed of the risks and benefits associated with treatment options and partner with the physician to incorporate personal preferences and values into the decision‐making process. This article identifies factors that influence decision‐making in treatment selection for patients with metastatic breast cancer and oncologists treating metastatic breast cancer.